The Psychosocial Struggles of Risking Emasculation and the Becoming of Real Hijra: Recounting Nirvana Process in Transwomen Life Narratives - D, Sakthi Brinda (International Journal of Psychosocial Rehabilitation, 2020)
Gender is more a cultural construct and a psychosocial identity than a biological factor. Yet, the transgender individuals face an enormous amount of social segregation and cultural stigma due to the gender to which they identify themselves. The prime cause of such a stigma seems to emanate from the fact that an apparent gap exists between the gender identity of transgender individuals and their biological sex as manifested by their body. The transgender individuals, in order to attain the perfect gender position to which they aspire for, desire hard to get rid of the sexual organs with which they were born, since the very same organs have become opposite to their gender at present. This is more the case with the transwomen or male-to-female (MTF) individuals, as their male genital organs turn out to be the source of stigma and social isolation especially in a country like India. In other words, the biological presence of male genital organs make the transwomen less female in their individual as well as sociocultural milieu. In order to get rid of their burdening male genital organ, the transwomen risk to get operated of their penis most often through a complicated surgery potential of leaving them dead or seriously ill. Within the transgender community in India, getting opportunity for this surgery is considered a huge blessing and a divine gift. The process of this surgery involves many rituals, community care and the individual’s huge suffering. Indian transgender life narratives are replete with vivid narrations of this process of sex reassignment surgery (SRS).In this paper, an attempt is made to trace the emasculation process undergone by the transwomen in typical Indian conditions so as to attain their “Nirvana” and become a “real” Hijra. The emasculation is effected by the SRS process involving a lot of preparation on the part of the transwomen and their community or family, brutal surgery, shabby post-operative care and their final relief of joining their Hijra community with a lot of attention, reception and special celebrations. This Nirvana process, as evinced from the life narratives of transwomen, hinges upon medical, anthropological and cultural paradigms of transwomen’s lives in India.